A unified approach to (‒)-FR901483 and (+)-TAN1251B - Girault, Malory P.Y. (2010)
This thesis describes studies, which have been realised towards the total syntheses of two natural products (–)-FR901483 (1) and (+)-TAN1251B (3), which are thought to be biosynthetically related.